Implementasi Kebijakan Penataan Pedagang Kaki Lima Di Kawasan Kaki Jembatan Suramadu Sisi Surabaya - Sandra, Dewi Ayu; Nawangsari, Ertien Rining (JIAP (Jurnal Ilmu Administrasi Publik), 2025)
The foot area of the Suramadu bridge on the Surabaya side is one of the most frequently visited locations in the city of Surabaya. The large number of visitors coming to the area has raised the interest of the surrounding community to become street vendors. The objective of this study is to describe the performance of the implementation of the street vendor arrangement policy in the foot area of the Suramadu bridge on the Surabaya side. This study uses a descriptive method with a qualitative approach. Data collection techniques in this study were carried out through observation, interviews, and documentation with the research informants involved. Theory of Policy Implementation by Van Meter and Van Horn consisting of: Policy standards and targets; Resources; Inter-organizational communication; Implementor characteristics; Implementer attitudes or tendencies; Economic, social and political conditions are the main references in identifying the results of this study. The results of this study indicate that the performance of the implementation of street vendor arrangements in the foot area of the Suramadu Bridge on the Surabaya side using the analysis of the implementation theory by Van Meter and Van Horn was less successful. This is due to the problems that occur so that street vendors are still free to trade in the area..